The Potential of Liming to Improve Drought Tolerance of Norway Spruce [Picea abies (L.) Karst.] - Kohler, Martin; Kunz, Jörg; Herrmann, Johannes; Hartmann, Peter; Jansone, Lelde; Puhlmann, Heike; von Wilpert, Klaus; Bauhus, Jürgen (Frontiers in Plant Science, 2019)
In response to a wide-spread decline in forest vitality associated with acid rain in the 1980s, liming of soils has been implemented in many federal states in Germany to buffer further acid deposition and improve availability of nutrients such as calcium and magnesium. As a consequence, it may also increase vitality and depth of fine-root systems and hence improve the drought tolerance of species such as Norway spruce (Picea abies (L.) Karst.), which occurs mostly on acidic forest soils. However, the influence of repeated liming on drought tolerance of trees has never been studied. Here we compared the resistance, recovery and resilience of radial growth in P. abies in relation to drought in limed and control stands and assessed how the dosage and interval between lime applica-tion and drought year influences the radial growth response of P. abies. We analyzed radial growth in 198 P. abies trees of six experimental sites in south-west Germany. An analysis of the radial increment over the last 30 years allowed the analysis of drought events shortly after the first liming (short-term effect) as well as posterior drought events (mid- to long-term effects). Generalized linear models were developed to assess the influence of drought intensity, site and period since first liming on the drought tolerance of Norway spruce. Regardless of drought intensity, there was no general increase in drought resistance of Norway spruce in response to liming. However, drought resistance of radial growth improved on a loamy site that was additionally treated with wood ash 30 years after the first lime application. Furthermore, recovery and resilience of radial growth after severe drought events were generally better in spruce trees of limed treatments. This indicates a shorter stress period in spruce trees growing on limed soil, which may reduce their susceptibility to secondary, drought-related pests and pathogens.